Carcass Traits and Value of Meat and Byproducts of Goat - Muthukumar, M.; Kandeepan, G.; Pathak, Vikas; Rathod, K. S.; Ambadkar, R. K.; Thomas, R.; Kulkarni, V.V. (Journal of Meat Science, 2019)
A study was conducted to collect data on carcass traits covering 1517 goats across India. The results indicated that the live weight and dressed carcass weight of goats ranged from 12.54 to 28.16 kg and 5.84 to 13.41 kg, respectively with an average dressing percentage of 46.86%. There was a significant difference (P<0.005) in the overall live weight, carcass weight, dressing percentage and overall yield of byproducts of goats of different body weight groups (viz., less than 15 kg (Group 1), between > 15 to < 20 kg (Group 2), >20 to <25 kg (Group 3) and more than 25 kg (Group 4) of different states. It was also found that the majority of the goats slaughtered were in the weight group of >15 to >20 kg (36.85 %). The overall average live weight of goats from Maharashtra (20.58 kg) and Andhra Pradesh (19.51 kg) were higher when compared to other states. Except skin, all the byproducts are utilized for human consumption and the yield of edible (blood, head, feet, stomach and intestine, heart, liver, lungs, kidney and fat) and inedible (skin) byproducts as percentage of live goat weight were 43.79 and 9.35 %, respectively. In terms of commercial value of goat carcass, major revenue comes from meat (81.07 – 85.78%), followed by edible offal (11.55 – 16.47%) and skin (2.39 – 2.68%).